Study of Death Incidence by Insecticide Poisoning in Salem - V., Selvam; PanneerSelvam, G.; V., Vijayanath (International Journal of Medical Toxicology and Forensic Medicine, 2012)
Background: Insecticide poisoning is a major public health problem in the world, particularly in developing nations, its usage has increased in recent and past thus increased even its misuse to commit suicide. Methods: This retrospective study was carried out at department of Forensic Medicine & Toxicology, Govt. Mohan Kumaramangalam Medical College Hospital Salem, Tamil Nadu, India with the insecticide poisoning cases from the year of 2008 and 2009. Age from 6 months old foetus to 80 years. All collected data was analyzed in SPSS software. Results: During this study period a total 2871 Medico legal autopsies were conducted, amongst them poisoning cases constitutes 372 (12.9%) cases, out of these 93 (25%) other poisoning cases, 279 (75%) cases were due to fatal insecticide poisoning. Conclusion: During the period of 2008 & 2009 there are 260 number of cases were reported as suicidal poisoning by insecticides out of 279 cases. Males were outnumbered with 170 cases and females were 109 cases. More number of the cases were found in the age group of 21–30 years(82) followed by 31-40 years (68). Peak period of deaths by poisoning more in nos. in the month of May & June. Most victims were from rural area, married population outnumbering the married. There are 212 (74.98%) victims were from rural area while 67(24.01%) were from urban area and 223 (79.92%) were married, 56 (20.07%) were unmarried. Key words : Insecticide poisoning; organophosphates; chemical report; Tik-20; follidol, suicide;